2001
DOI: 10.1002/1529-0131(200101)44:1<105::aid-anr14>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of differentiated dendritic cell infiltration of autoimmune and osteoarthritis synovial tissue

Abstract: Objective Infiltration of rheumatoid arthritis (RA) synovial tissue (ST) by differentiated dendritic cells (DC) is a consistent feature in patients with active disease. However, mononuclear cells (MNC), including DC, may be nonspecifically chemoattracted to inflammatory sites regardless of etiology. Therefore, to evaluate the specificity of ST infiltration by differentiated DC, synovial biopsies from patients with RA, spondylarthropathy (SpA), osteoarthritis (OA), and gout were examined. Methods Formalin‐fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
12
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 15 publications
(27 reference statements)
5
12
0
Order By: Relevance
“…Correspondingly, infiltration of ST by macrophages and the expression of macrophage-derived cytokines in ST of patients with RA have been noted [39][40][41]. A recent study demonstrates a close correlation between differentiated DCs infiltration, lymphocytic infiltration and vascularity in ST from patients not only with RA, but also with osteoarthritis and spondyloarthropathy, suggesting common factors mediating the migration of DCs and lymphocytes into damaged joints [42].…”
Section: Discussionmentioning
confidence: 90%
“…Correspondingly, infiltration of ST by macrophages and the expression of macrophage-derived cytokines in ST of patients with RA have been noted [39][40][41]. A recent study demonstrates a close correlation between differentiated DCs infiltration, lymphocytic infiltration and vascularity in ST from patients not only with RA, but also with osteoarthritis and spondyloarthropathy, suggesting common factors mediating the migration of DCs and lymphocytes into damaged joints [42].…”
Section: Discussionmentioning
confidence: 90%
“…Several authors reported that macrophages and T cells are the most abundant cells 8,9,11,17,20,21,25,34,35,37,45,47,48,51,56,57,61,62,69,78 . Mast cells (MCs) 49,50,54,55,58e60,64,67,70,79 , as well as B cells and plasma cells were found, although the last two in lower amounts than other cells 9,11,21,24,25,33e35,44,45,57,69,73 .…”
mentioning
confidence: 99%
“…Mast cells (MCs) 49,50,54,55,58e60,64,67,70,79 , as well as B cells and plasma cells were found, although the last two in lower amounts than other cells 9,11,21,24,25,33e35,44,45,57,69,73 . Natural killer cells were detected in OA ST 65 and several authors describe the presence of low numbers of dendritic cells (DCs) 8,53,66,69 . Neutrophils were almost never found 21,34,35,44,48,62 .…”
mentioning
confidence: 99%
“…The NF-B transcription factor pathway plays a key role in the differentiation, activation, and survival of almost all cells in the body. In RA, active NF-B is localized in the nucleus of hemopoietic and parenchymal cells (2)(3)(4). Moreover, previous studies of NF-B inhibitors in animal models of RA demonstrated the important role played by NF-B in the production of mediators of inflammation in the joint and the antiinflammatory effect of such inhibitors (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%